Pengaruh Jumlah Total Produksi dan Safety Stock terhadap Pemenuhan Permintaan pada UMKM Leven Coffe Roaster - Yahya, Lucky Mahesa; Hasanah, Ainilla; Hutasuhut, Nadra Nadila; Firdaus, Riska Maharani (BUDGETING : Journal of Business, Management and Accounting, 2023)
When running a business, of course you need to prepare things that can support the business being run thoroughly. Determining the amount of inventory and production is also important in supporting business success. Likewise with Leven Coffee Roaster MSMEs which of course also have their own inventory and production quantities to run their business. The aim of this research is to see how much influence the amount of inventory and production has on demand for Leven Coffee Roaster MSMEs. In conducting this research, the method used was a quantitative method. In an effort to obtain this data, researchers used the interview method with MSME owners. For data processing, researchers used the multiple linear regression method to help researchers determine the influence of variable X on Y. From the test results it was found that variable The remaining 65.4% is influenced by other variables outside the variables studied.